Biochar as an agrifood innovation: evidence and lessons for integration into agricultural landscapes - Somorin, Tosin; Akanno, C.; Osei-Amponsah, Charity; Gebrezgabher, Solomie A.; Mupangwa, Walter; Adamtey, Noah; Nartey, Eric Gbenatey; Lord, R.; Ennis, C.; Zhang, X.; Fletcher, A.; Lue, L.; et al. (International Water Management Institute, 2025)
This report examines biochar as an agrifood innovation within circular bioeconomy and multifunctional landscape frameworks, with a focus on its relevance for smallholder agriculture in the Global South. Produced from organic residues through thermochemical processes, biochar offers a pathway to restore degraded soils, valorize waste, and support climate mitigation and adaptation. Evidence shows that biochar can improve soil structure, nutrient retention, and water-holding capacity, enhancing crop resilience in sandy and drought-prone environments while reducing reliance on synthetic inputs. However, its effectiveness is highly context-dependent. Outcomes vary with feedstock quality, production technology, soil conditions, and application practices. Risks include inconsistent agronomic performance, potential contamination, feedstock competition, and uncertain climate benefits when full life-cycle impacts are overlooked. Slow pyrolysis is the most suitable option for low-cost, rural settings, while advanced technologies remain less accessible. Biochar is therefore neither a silver bullet nor a flawed concept, but a promising tool whose benefits depend on careful design, regulation, and integration into locally appropriate, inclusive systems.